The effects of ecstatistakes on students' academic performance and intention to play educational board games - Calibara, Joanna Marie A (Miagao, Iloilo University of the Philippines Visayas, 2021)
Yjis study was conducted in order to determine the effect of the educational board game, Ecstatistakes in the students' academic performance in trigonometry and to their intention to play educational board games. The main objective is to determine whether or not the educational board game positively affects the students' academic performance and to identify whether or not there are changes on their level of intention to play educational board games. In addition to that, this study aimed to identify the different factors that affect students' engagement in playing educational board games. this study was conducted in SY 2018-2019 involving 104 Grade 9 students of a certain private school in Iloilo City. In this quasi-experimental study, the students' sex and mathematical ability level was used as independent variables. The researcher utilized the researcher-made assessment tools, Educational Board Playing Intention Scale questionnnaire, written feedbacks, and focus group discussion. To determine students' academic performance, data from pre-test and post-test assessments were analyzed using the mean, standard deviation, Kruskal-Wallis test, and Mann-Whitney test. To determine the level of intention, data from written feedbacks and focus group discussions were analyzed using thematic analysis. The result of the study showed that palying educational board games significantly increased students' academic performance but not their level of intention to play educational board games. It was also found out that the following are the factors that affect students' engagement in educational board game: game mechanics, questions and answer keys provided, association with others, and benefits of the game.
Special Problem (MEd-Mathematics) -- Miagao, Iloilo : U.P. Visayas, July 2021.
Keywords: Educational board games; Ecstatistakes -- Board games